2019
DOI: 10.3390/s19184051
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-Damage Detection in Lemons Using Electrochemical Impedance Spectroscopy

Abstract: Lemon is the most sensitive citrus fruit to cold. Therefore, it is of capital importance to detect and avoid temperatures that could damage the fruit both when it is still in the tree and in its subsequent commercialization. In order to rapidly identify frost damage in this fruit, a system based on the electrochemical impedance spectroscopy technique (EIS) was used. This system consists of a signal generator device associated with a personal computer (PC) to control the system and a double-needle stainless ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Compared to previously mentioned works, presenting a 90% precision in the determination of avocado post-harvest ripening degree 28 using ANN and 100% in the discrimination of frozen lemons using SVM 29 , the on-plant discrimination of strawberry ripening degree (0.72 F -score, MLP-1) resulted to be less effective. On the other hand, such works were carried out with a smaller number of fruit samples (respectively 100 and 180, compared to the 923 used in this work) and do not indicate if the test set was left unseen until the final classification task or was used in the training.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Compared to previously mentioned works, presenting a 90% precision in the determination of avocado post-harvest ripening degree 28 using ANN and 100% in the discrimination of frozen lemons using SVM 29 , the on-plant discrimination of strawberry ripening degree (0.72 F -score, MLP-1) resulted to be less effective. On the other hand, such works were carried out with a smaller number of fruit samples (respectively 100 and 180, compared to the 923 used in this work) and do not indicate if the test set was left unseen until the final classification task or was used in the training.…”
Section: Resultsmentioning
confidence: 56%
“…Nevertheless, all these works lack of well-established machine learning methods predicting the fruit ripening stage starting from bioimpedance data. The most relevant works in this specific field describe the application of support-vector machine algorithms to the classification of avocado ripening degree 28 and the detection of freeze damage in lemons using artificial neutral networks and principal component analysis 29 . Both papers achieved a good accuracy in the classification task, obtaining a 90% (SVM) and 100% (ANN) precision, training the models with a total 100 and 180 samples, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…(5), where Z j j is the modulus of impedance and θ is the phase angle. Previous studies have reported that freezing level can be identified through impedance parameters (Aboalnaga, Said, Madian, & Radwan, 2019;Fernández, Pinatti, Peris, & Laguarda-Miró, 2019;Liu et al, 2017;Ohnishi, Fujii, & Miyawaki, 2002;Vidaček, Medi c, Botka-Petrak, Nežak, & Petrak, 2008). These parameters, such as resistance and reactance, have an imperfect ability to investigate internal changes of a tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, all these works lack of well-established machine learning methods predicting the fruit ripening stage starting from bioimpedance data. The most relevant works in this specific field describe the application of support-vector machine algorithms to the classification of avocado ripening degree 28 and the detection of freeze damage in lemons using artificial neutral networks and principal component analysis 29 . These works, despite being a good starting point for the use of a combined bioimpedance and machine learning approach for the evaluation of fruit quality, lack in the amount of considered data to develop the models and most importantly do not provide a detailed data analysis pipeline, which is strongly needed as a reference in the development of similar works.…”
Section: Introductionmentioning
confidence: 99%